Function-Sparing Free Split Latissimus Dorsi Flap for Lower-Extremity Reconstruction: Five-Year Consecutive Single-Surgeon Series. (July 2020) - Chim, Harvey; Cohen-Shohet, Rachel; McLaughlin, Mariel M.; Ehanire, Tosan
Abstract : Background: The free split latissimus dorsi flap for lower-extremity reconstruction has some advantages over the traditional latissimus dorsi flap. The flap is harvested with the patient in the supine position and is associated with minimal morbidity as the function of the remaining latissimus dorsi muscle is preserved through the posterior division of the thoracodorsal nerve. Methods: A consecutive single-surgeon 5-year series of free split latissimus dorsi muscle flaps for lower-extremity reconstruction (n = 42) was evaluated. Donor site morbidity was evaluated through assessment of the strength of the remaining latissimus dorsi at least 1 month after surgery. Shoulder function was evaluated postoperatively using the Disabilities of the Arm, Shoulder and Hand (DASH) score, American Shoulder and Elbow Surgeons (ASES) score, and Shoulder Pain and Disability Index (SPADI). Results: The mean age of the 42 patients was 40.7 years. The mean length and width of the flaps were 17.9 cm and 8.6 cm. The majority (71%) of the wounds were due to acute trauma. Of the 42 flap procedures performed, 95% (40) were successful. Assessment of remaining latissimus dorsi strength at least 1 month postoperatively, during 3 activities, showed a Medical Research Council (MRC) grade of 5 in all patients. The mean and median scores were 6.4 and 0 according to the DASH, 6.0/6.4 and 0/0 on the SPADI pain/disability scales, and 90.7 and 100 on the ASES. Conclusions: The free split latissimus dorsi flap is a large reliable muscle flap with negligible donor site morbidity that is particularly advantageous for lower-extremity resurfacing following trauma. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.